CF derived scoring systems do not fully describe the range of structural changes seen on CT scans in PCD. Issue 4 (21st January 2019) - Tadd, Katelyn; Morgan, Lucy; Rosenow, Tim; Schultz, André; Susanto, Clarissa; Murray, Conor; Robinson, Philip
Abstract: Background: Structural lung changes seen on computed tomography (CT) scans in Cystic Fibrosis (CF) and Primary Ciliary Dyskinesia (PCD) are currently described using scoring systems derived from CF populations. This practise assumes lung damage in the two conditions is identical, potentially resulting in a failure to identify PCD‐specific changes. Our study addresses this assumption. Methods: A total of 58 CT scans from 41 PCD patients (age 2‐48 years) were examined and the presence and extent of abnormalities common in CF; bronchiectasis, bronchial wall thickening, atelectasis, mucous plugging, and air trapping noted. Further assessment of the PCD scans by an experienced chest radiologist identified several unique PCD specific changes. Results: Bronchial wall thickening was the commonest abnormality seen in PCD. All abnormalities were present more often in middle and lower lobes than in upper lobes ( P  < 0.001). Bronchiectasis, mucus plugging, atelectasis, and air trapping were present more often in PCD than in the historic CF cohorts which formed the basis of two CF scoring systems ( P  < 0.05). Extensive tree‐in‐bud pattern of mucus plugging, thickening of interlobar, and interlobular septa, and whole lobe atelectasis were seen significantly more frequently in PCD than CF. Conclusions: Structural changes identified on CT scans in PCD are not identical to those previously described in CF patients and suggest assessment of PCD structural changes on CT should not use CF derived scoring systems.